Alterations of neuronal precursor cells in stages of human adult neurogenesis in heroin addicts. (1st November 2015) - Bayer, Ronny; Franke, Heike; Ficker, Christoph; Richter, Monique; Lessig, Rüdiger; Büttner, Andreas; Weber, Marco
Highlights: The human hippocampus was examined using markers indicative of neuronal precursors. Heroin addicts were compared to controls. A decrease of precursor cells was detected in drug addicts. Age-dependent increase of Musashi-1 expression is inhibited in addicts. Drug addiction is associated with decreased calretinin fibre staining. Abstract: Background: Adult neurogenesis has been shown to occur throughout life and different brain pathologies were demonstrated to be associated with altered neurogenesis. Here, an impact of heroin addiction on neurogenesis in humans is hypothesised. Methods: Post mortem hippocampal specimens of drug addicts with known heroin abuse and a group of non-addictive control subjects were analysed, using antibodies indicating different stages of neurogenesis. The subgranular zone of the dentate gyrus was examined qualitatively and quantitatively. Results: The data indicate (i) a decreased number of neural precursor cells, (ii) accompanied by low rates of proliferation and (iii) a marked loss of dendritic trees in targeting cells in heroin fatalities. (iv) The age-dependent increase of differentiating cells in the healthy controls was not observed in the addicts. Additionally, double immunofluorescence labelling indicated the precursor nature of Musashi-1 positive cells in the human subgranular zone of the dentate gyrus. Conclusions: Present data firstly demonstrate the influence of drug addiction with known heroin abuse on different developmental stages of progenitors in the dentate gyrus. The patterns of antibody staining suggest a distinct inhibition of neurogenesis at the stage of neural precursor cells and revealed morphological changes in targeting cells in cases of heroin addicts as compared to healthy controls. These alterations could be considerable for memory and cognitive deficits as well as addictive behaviour in chronic drug abusers and may give rise to specific pro-neurogenic therapies.